INTEGRATING TORAJA CULTURAL VALUES INTO ENGLISH LANGUAGE TEACHING: A COMPREHENSIVE ANALYSIS (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
The objective of this study was to find out the cultural values were implemented by teachers in learning English. This study implemented descriptive qualitative study. Data were collected through observation, recording, and interviews with four English teachers. The subjects of this study were chosen by using purposive sampling. And using Miles and Huberman's theory to analyze the data. The results of the study show that there were several Toraja cultural values in learning English activity, namely: a) the values of kapatonganan (religiousness), b) the values of kasiuluran (Family), c) the values of tengko situru’ (togetherness), c)  the values of kabassaran (work hard), d) the values of longko'/siri' (tolerance/shame/authority), e) the value of ma'parapa' (love peace), f) the value of sikamali' (affection), g) the value of siangkaran (help), h) the value of mabalele (friendly/communicative), i) the value of umpangke' tomendadianna (respect for parents). Based on the results above, the writer  concluded that in learning English process at SMK 1 Toraja Utara, the teacher presented the English material by incorporating cultural values of Toraja.
Keywords: Cultural; Value; Toraja; English Language; teaching.